Bats in the Anthropocene: Conservation of Bats in a Changing World 2015
DOI: 10.1007/978-3-319-25220-9_7
|View full text |Cite
|
Sign up to set email alerts
|

Dark Matters: The Effects of Artificial Lighting on Bats

Abstract: While artificial lighting is a major component of global change, its biological impacts have only recently been recognised. Artificial lighting attracts and repels animals in taxon-specific ways and affects physiological processes. Being nocturnal, bats are likely to be strongly affected by artificial lighting. Moreover, many species of bats are insectivorous, and insects are also strongly influenced by lighting. Lighting technologies are changing rapidly, with the use of light-emitting diode (LED) lamps incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 118 publications
(200 reference statements)
1
80
0
1
Order By: Relevance
“…Past studies have found both negative and positive consequences of artificial light for bats [55,56]. Our working hypothesis is that artificial light will change the bat assemblage foraging at the lit site compared with the assemblage foraging at the dark site.…”
Section: Monitoring Of Bats As a Group Of Obligatory Nocturnal Mammalsmentioning
confidence: 97%
See 1 more Smart Citation
“…Past studies have found both negative and positive consequences of artificial light for bats [55,56]. Our working hypothesis is that artificial light will change the bat assemblage foraging at the lit site compared with the assemblage foraging at the dark site.…”
Section: Monitoring Of Bats As a Group Of Obligatory Nocturnal Mammalsmentioning
confidence: 97%
“…In contrast, bats with a more rural distribution pattern, such as Pipistrellus nathusii should be less abundant at the lit than at the dark site since they are generally more light-averse. Similarly, species that usually forage in cluttered space should be less abundant at the lit site because they are adapted to the dark interior of their forest habitat and might be particularly light-averse [56,59].…”
Section: Monitoring Of Bats As a Group Of Obligatory Nocturnal Mammalsmentioning
confidence: 99%
“…a portable LED outdoor lamp emitting normal white light (produced by McMantom, Italy). The lamp's light spectrum had a bimodal pattern typical of LED lighting (Rowse et al, 2016) with two peaks of relative luminous flux at 450 nm and 590 nm (data provided by the producer). We powered the light with a 12V (35A) car battery switched on manually.…”
Section: Fieldworkmentioning
confidence: 99%
“…Besides repelling most bat species, ALAN at foraging sites may disrupt communities of prey insects (e.g. Moreover, illuminating the surroundings of feeding sites may sever bat commuting routes (Stone et al, 2009;Polak et al, 2011;Hale et al, 2015), or drive insects away from neighbouring habitats, exerting a sort of "vacuum cleaner" action that reduces food availability (Rowse et al, 2016). Moreover, illuminating the surroundings of feeding sites may sever bat commuting routes (Stone et al, 2009;Polak et al, 2011;Hale et al, 2015), or drive insects away from neighbouring habitats, exerting a sort of "vacuum cleaner" action that reduces food availability (Rowse et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the impact of ALAN on the environment [5] and there is a growing concern that LP affects biodiversity [6,7]. Until recently, the main focus of studies about ecological LP was on terrestrial animals [5,[8][9][10] and plants [10,11]. However, because human settlements concentrate along freshwater reservoirs and coastlines, research on ecological LP has shifted towards aquatic systems [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%